Increased serum laminin and angiogenin concentrations in patients with peripheral arterial occlusive disease. Issue 6 (June 1996) - Burgmann, H; Hollenstein, U; Maca, T; Zedwitz-Liebenstein, K; Thalhammer, F; Koppensteiner, R; Ehringer, H; Graninger, W
Abstract : AIM: To measure serum laminin and angiogenin concentrations in patients with peripheral arterial occlusive disease (PAOD) Fontaine stages IIb, III, and IV. METHODS: The study population comprised 38 patients (20 men and 18 women) with stage IV PAOD, 11 patients (six men and five women) with stage III PAOD, 18 patients (10 men and eight women) with stage IIb PAOD, and 23 patients (10 men and 13 women) with deep vein thrombosis. Fifteen normal subjects (matched for risk factors) and 10 patients (five men and five women) without PAOD served as controls. Serum samples were obtained at admission and serum laminin and angiogenin concentrations were measured using an enzyme linked immunosorbent assay. RESULTS: Patients with stage IV PAOD had higher serum laminin (mean +/- SEM; 826 +/- 97 ng/ml) and angiogenin concentrations (467 +/- 26 pg/ml) than normal subjects (laminin: 379 +/- 21 ng/ml; angiogenin: 358 +/- 16 pg/ml) and patients without PAOD (laminin: 277 +/- 34 ng/ml; angiogenin: 406 +/- 25 pg/ml). A significant correlation was found between angiogenin and laminin and between serum laminin and fibrinogen concentrations in patients with stage IV disease. CONCLUSIONS: Raised laminin and angiogenin concentrations may be indicators of endothelial damage caused by reduced vascular perfusion or compensatory revascularisation, or both.